A combined association of obesity, alanine aminotransferase and creatinine with hyperuricemia in youth aged 13–20 years - Niu, Yang; Zhang, Yajie; Sun, Yan; Sheng, Jinye; Lu, Wenyi; Li, Ji; Mao, Xiaomeng; Feng, Yi; Shen, Xiuhua (Frontiers in Nutrition, 2024)
Background: Despite extensive research on hyperuricemia (HUA) in adults, there remains a dearth of studies examining this condition in youth. Consequently, our objective was to investigate the prevalence of HUA among youth in the United States, as well as identify the corresponding risk factors.This study employed a nationally representative subsample of 1051 youth aged 13-20 from the US National Health and Nutrition Examination Survey (NHANES) conducted between January 2017 and March 2020. Univariate and multivariate techniques were utilized to examine the association between HUA and obesity, dietary nutrients, liver and kidney function, glucose and lipid metabolism, inflammation, and other indicators in the adolescent population.The study encompassed a cohort of 1051 youth aged 13-20 years, comprising 538 boys and 513 girls. The overall prevalence of HUA was found to be 7% (74 out of 1051). Univariate analysis revealed that the HUA group exhibited greater age, body mass index (BMI), waist circumference (WC), hip circumference (HC), and waist-to-hip ratio (WHR). Additionally, the prevalence of obesity was significantly higher in the HUA group compared to the non-HUA group (all P<0.05). Regarding biochemical indicators, the levels of urea nitrogen, creatinine (Cr), alanine aminotransferase (ALT), glutamic oxalic aminotransferase (AST), gamma-glutamyl transferase (GGT), total cholesterol (TC), triglyceride (TG), and HS C reactive protein (Hs CRP) were found to be significantly higher in the HUA group compared to the non-HUA group (all P<0.05). Further analysis using binary logistics regression showed that BMI (P=0.024, OR1.158, 95%CI1.019-1.316), ALT (P=0.020, OR1.032, 95%CI1.005-1.059), and Cr (P=0.016, OR1.028, 95%CI1.005-1.051) were identified as risk factors for HUA, after controlling for age, gender, BMI, WC, HC, WHR, ALT, AST, GGT, TG, TC, Cr, Hs CRP, and other indicators. Interestingly, neither univariate nor multivariate analysis found any association between dietary nutrients and the risk of HUA (all P>0.05).Conclusions: High BMI remains a major risk factor for HUA in US youth aged 13-20 years, and ALT and Cr levels should be closely monitored along with serum uric acid.